Novel supramolecular assembly of 3,5-dinitro-4-methylbenzoic acid and trans-1,2-bis(4-pyridyl)ethene - Varughese, S; Pedireddi, VR (Tetrahedron Letters, 2005)
A novel organic assembly, formed between 3,5-dinitro-4-methylbenzoic acid and trans-1,2-bis(4-pyridyl)ethene under hydrothermal conditions in the presence of Pr(III) and a layered structure obtained by direct co-crystallization of the reactants at ambient conditions is reported. The structures of the complexes were established, unambiguously, by single crystal X-ray diffraction methods. (c) 2005 Elsevier Ltd. All rights reserved.